Antipodean agricultural and resource economics at 60: agricultural adjustment1. (26th August 2016) - Edwards, Geoff; Bates, Winton
Abstract : Over the last 60 years, Australian and New Zealand agricultural economists have promoted a better understanding of agricultural adjustment pressures and opportunities among farmers and policy makers. They have emphasised that adjustment pressures faced by farmers are linked to economy‐wide growth processes and that adjustment problems have been aggravated by past government policies, including closer settlement and measures distorting markets for agricultural outputs and inputs. Economists who argued that provision of adjustment assistance would be preferable to price support policies helped to change the focus of agricultural policy toward facilitating adjustment. When rural adjustment schemes were established in the early 1970s, the case for them was made largely in terms of impediments to efficient adjustment in capital and labour markets. However, the schemes involved elements of 'government failure', especially concessional interest rates. Over the following decades, as economists became increasingly sceptical about market failure rationales, adjustment assistance schemes gradually became decreasingly important. Nevertheless, there is ongoing support for the view that adjustment assistance can sometimes enable less efficient and less equitable polices to be avoided.